EFEKTIVITAS PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KAWASAN KUMUH MUARA ABU KELURAHAN OESAPA BARAT KECAMATAN KELAPA LIMA KOTA KUPANG - Pariangu, umbuUmbu TW; Nainel, Milyesdehimne (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
Muara Abu, located in Oesapa Barat Urban Village, Kelapa Lima Sub-District, Kupang City, is one of the priority areas for the implementation of the KOTAKU Program. This area has a chaotic building layout, poor road conditions, lack of waste facilities, inefficient waste system, minimal clean water supply from PDAM or has not met the criteria for clean water minimum service standards (SPM), environmental road conditions, drainage, and wastewater management systems, which do not meet technical standards and health aspects. This study aims to determine the effectiveness of the programme implementation using input, process and output variables. Each stage is described through analysis to obtain coherence so that it can be concluded whether the KOTAKU Programme has been effective or otherwise. This research uses a qualitative approach with a descriptive research type. Data was collected using observation, interview and documentation techniques, then analysed through data reduction, data presentation and conclusion drawing. The results showed that the implementation of the KOTAKU Programme in Muara Abu has not been effective from the input-process and output aspects as a whole. Some infrastructure has been built to change the landscape of the region. However, holistically, the program has not been able to stimulate support and active participation from the community to contribute ideas and positive behaviour for the continuity of the program's impact. The Kupang City Government also needs to regularly evaluate the implementation of the KOTAKU Programme to ensure that the facilities built are in line with quality and sustainability requirements.